Concurrent validity of inertial measurement units in range of motion measurements of upper extremity: A systematic review and meta-analysis - Jinfeng Li; Fanji Qiu; Liaoyan Gan; Li-Shan Chou (Wearable Technologies, 2024)
Inertial measurement units (IMUs) have proven to be valuable tools in measuring the range of motion (RoM) of human upper limb joints. Although several studies have reported on the validity of IMUs compared to the gold standard (optical motion capture system, OMC), a quantitative summary of the accuracy of IMUs in measuring RoM of upper limb joints is still lacking. Thus, the primary objective of this systematic review and meta-analysis was to determine the concurrent validity of IMUs for measuring RoM of the upper extremity in adults. Fifty-one articles were included in the systematic review, and data from 16 were pooled for meta-analysis. Concurrent validity is excellent for shoulder flexion–extension (Pearson’s r = 0.969 [0.935, 0.986], ICC = 0.935 [0.749, 0.984], mean difference = −3.19 (p = 0.55)), elbow flexion–extension (Pearson’s r = 0.954 [0.929, 0.970], ICC = 0.929 [0.814, 0.974], mean difference = 10.61 (p = 0.36)), wrist flexion–extension (Pearson’s r = 0.974 [0.945, 0.988], mean difference = −4.20 (p = 0.58)), good to excellent for shoulder abduction–adduction (Pearson’s r = 0.919 [0.848, 0.957], ICC = 0.840 [0.430, 0.963], mean difference = −7.10 (p = 0.50)), and elbow pronation–supination (Pearson’s r = 0.966 [0.939, 0.981], ICC = 0.821 [0.696, 0.900]). There are some inconsistent results for shoulder internal–external rotation (Pearson’s r = 0.939 [0.894, 0.965], mean difference = −9.13 (p < 0.0001)). In conclusion, the results support IMU as a viable instrument for measuring RoM of upper extremity, but for some specific joint movements, such as shoulder rotation and wrist ulnar-radial deviation, IMU measurements need to be used with caution.